Slope Analysis Based On SRTM Digital Elevation Model Data: Study Case On Rokan IV Koto Area And Surrounding - Choanji, Tiggi (Kopertis Wilayah X)
The level of slope influenceed by the condition of the rocks beneath the surface. On high level of slopes, amount of surface runoff and water transport energy is also enlarged. This caused by greater gravity, in line with the surface tilt from the horizontal plane. In other words, topsoil eroded more and more. When the slope becomes twice as steep, then the amount of erosion per unit area be 2.0 - 2.5 times more. The area of study are include in Rokan IV Koto area that can be accessed through the road from Ujung Batu City toward west up to Banjar Datar village. Based on SRTM data obtained, the roads in study area has a minimum elevation of + 80 m and a maximum + 545 m. Rugged road conditions with slope ranging from 2 ° to 47.84 ° causing this area having potential of landslides. The purpose of this study is to map the locations that have fairly steep slopes and potential landslides.